Children's, parents', and other stakeholders' perspectives on the factors influencing the initiation of early dietary change in the management of childhood chronic disease: a mixed studies systematic review using a narrative synthesis. Issue 4 (April 2021) - Pugh, Pearl; Hemingway, Pippa; Christian, Martin; Higginbottom, Gina
Highlights: Education is a key driver of dietary knowledge. Targeting the family leaders of diet and lifestyle change encourages whole-family buy-in. Dietary change should be considered as part of the early management of many paediatric chronic diseases. Practical, culturally relevant workshops are key to early dietary change. Shared experiences provide families with important engagement, motivating long-term change. Barriers to accessing and implementing change need addressing. There is a paucity of research on the child, parent, and healthcare professional's perspective on the factors influencing the initiation of early dietary change in the management of childhood chronic disease. Abstract: Background: Early dietary change can provide vital medical benefits supporting childhood chronic disease self-management. Objective: To explore factors influencing the initiation of early dietary change in the management of childhood chronic disease, as described by children, parents', and other stakeholders, to inform practice change in early paediatric service delivery. Methods: This systematic review crossed seven databases from 2000-2018 to identify empirical research (qualitative, quantitative, and mixed-method designs), including grey literature. Methodological quality was appraised using validated scoring systems. Results: Six studies met our criteria for inclusion in the review. Four themes of early dietary change emerged from these studies: (1) the role of education; (2) parents/caregivers' roles; (3) the role of self-management, and the (4) identification of enablers and barriers to dietary change. Conclusion: Obtaining the perspectives of children, parents' and other stakeholders' on factors influencing early dietary change is key to the self-management of childhood chronic disease. Practice implications: Early dietary change provides an essential resource in the self-management of many chronic diseases. In collaboration, children, parents' and healthcare professionals recognise the value of regular, engaging education, supported by workshops to empower and upskill, enabling change in everyday dietary habits, while using enablers and recognising challenges.